2002
DOI: 10.1302/0301-620x.84b2.0840202
|View full text |Cite
|
Sign up to set email alerts
|

The position of the tourniquet on the upper limb

Abstract: O ur aim was to determine if a tourniquet placed on the forearm has any advantage in clinical practice over the usual position on the upper arm. We randomised 50 patients who were undergoing an open operation for carpal tunnel syndrome under local anaesthesia into two groups. One had a tourniquet on the upper arm and the other on the forearm. The blood pressure, pulse, and level of pain were recorded at intervals of five minutes during the operation. The surgeons were also asked to evaluate the quality of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…Firstly, the majority of hand procedures undertaken under local anaesthesia, such as carpal tunnel release, trigger finger release, etc., are more easily carried out under a tourniquet and can be carried out within this time duration (Edwards et al, 2000). Secondly, previous studies performed on healthy people have identified that 20 minutes of tourniquet application is the reported average tolerance duration of an upper arm tourniquet (Edwards et al, 2000; Maury and Roy, 2002; Odinsson and Finsen, 2002; Yousif et al, 1993). Our study confirmed that the majority of subjects tolerated the tourniquet relatively well for 21 minutes, as the mean VAS at this time was 5.3 of a maximum of 10.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the majority of hand procedures undertaken under local anaesthesia, such as carpal tunnel release, trigger finger release, etc., are more easily carried out under a tourniquet and can be carried out within this time duration (Edwards et al, 2000). Secondly, previous studies performed on healthy people have identified that 20 minutes of tourniquet application is the reported average tolerance duration of an upper arm tourniquet (Edwards et al, 2000; Maury and Roy, 2002; Odinsson and Finsen, 2002; Yousif et al, 1993). Our study confirmed that the majority of subjects tolerated the tourniquet relatively well for 21 minutes, as the mean VAS at this time was 5.3 of a maximum of 10.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional IVRA has become less popular because the possibility of accidental release of the tourniquet would add the life threatening risk of LAST [14] , which can be avoided by the use of smaller non-toxic doses of LA in FA-IVRA. However, the position of the tourniquet on FA may pose some difficulty to the surgeon when operating proximal to the wrist [15] . Regarding the comparison between NTG and fentanyl as adjuvants to lidocaine in IVRA, we couldn't find a single study comparing the effects of both agents.…”
Section: Discussionmentioning
confidence: 99%
“…Lint from these materials can become embedded in the fasteners and reduce the effectiveness, possibly leading to an unexpected release of the cuff during the procedure. Tourniquet cuffs should be applied to the verified operative extremity in a location with adequate muscle mass to protect nerves and vessels. Upper arm and thigh tourniquets should be positioned on the limb at the point of maximum circumference proximal to the incision 18,19 Forearm tourniquets should be positioned mid‐forearm 18,19 …”
Section: Purposementioning
confidence: 99%
“… Upper arm and thigh tourniquets should be positioned on the limb at the point of maximum circumference proximal to the incision 18,19 Forearm tourniquets should be positioned mid‐forearm 18,19 Calf tourniquets should be placed with the proximal edge on the largest area of calf circumference 20 …”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation